The geology of Tianshui‐Qin'an area of the western Loess Plateau and the chemical characteristics of its Neolithic pottery - Ma, Hongjiao; Hein, Anke; Henderson, Julian; Ma, Qinglin (John Wiley and Sons Inc., 2020)
The difference in the chemical compositions between Neolithic pottery from the eastern and western ends of the northern Chinese Loess Plateau has been known for some time and a number of possible explanations have been proposed. However, a full understanding of the difference is yet to be achieved. Based on recent geological studies of the Tianshui-Qin’an area on the western Loess Plateau, the present study establishes a logical connection between the chemical characteristics of Neolithic pottery from the western Loess Plateau and the primary sediments available in the area. Moreover, this study reveals that the chemical compositions of clay used for fine wares and coarse wares at Dadiwan also bear some clear differences. Based on these findings, the paper discusses possible clay selection methods by potters in the Neolithic western Loess Plateau to make their different wares based on the locales where suitable raw materials are available. The paper demonstrates that the raw materials available for pottery making on the eastern and western Loess Plateau differ significantly and this explains the marked difference in ceramic composition between the two locations.